Pengembangan Kendaraan Listrik Hemat Energi untuk Transportasi Kota yang Ramah Lingkungan - Nur Kamaludin Al-Fatih; Iqbal Kartiko; Rudolf Fredric W Jala Watu Jr; Dika Ayu Safitri (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Air pollution and greenhouse gas emissions produced by motorized vehicles are one of the main problems in big cities. This encourages the development of more energy efficient and environmentally friendly vehicles, such as electric vehicles. This journal discusses the development of energy-efficient electric vehicles for urban transportation, with a focus on battery technology, vehicle design, and charging infrastructure. This research aims to develop energy-efficient electric vehicles that can meet city transportation needs. This research focuses on several aspects, namely: Lightweight and aerodynamic vehicle design: This design can reduce energy consumption and increase vehicle efficiency. Efficient propulsion system: An efficient propulsion system can increase mileage and reduce exhaust emissions. Advanced battery technology: Advanced battery technology can increase energy density and battery life. It is hoped that the results of this research will produce energy-efficient electric vehicles that are environmentally friendly and can help reduce air pollution in big cities.